Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1177/2211068213499758
|View full text |Cite
|
Sign up to set email alerts
|

Capture and Exploration of Sample Quality Data to Inform and Improve the Management of a Screening Collection

Abstract: A new approach to the storage, processing, and interrogation of the quality data for screening samples has improved analytical throughput and confidence and enhanced the opportunities for learning from the accumulating records. The approach has entailed the design, development, and implementation of a database-oriented system, capturing information from the liquid chromatography-mass spectrometry capabilities used for assessing the integrity of samples in AstraZeneca's screening collection. A Web application h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Data processing was performed using Analytical Data Reviewer (Virscidian, Cary, NC), which processed the raw instrument files, calculated the UV percent purity for the target chromatographic peak, and determined if the correct monoisotopic mass peaks were found in the mass spectra. 10 After automated processing by Analytical Data Reviewer, manual review was then performed for all samples with nongreen (<75% of confirmed purity) results. On average, about 40% of samples on each plate underwent manual review.…”
Section: Methodsmentioning
confidence: 99%
“…Data processing was performed using Analytical Data Reviewer (Virscidian, Cary, NC), which processed the raw instrument files, calculated the UV percent purity for the target chromatographic peak, and determined if the correct monoisotopic mass peaks were found in the mass spectra. 10 After automated processing by Analytical Data Reviewer, manual review was then performed for all samples with nongreen (<75% of confirmed purity) results. On average, about 40% of samples on each plate underwent manual review.…”
Section: Methodsmentioning
confidence: 99%
“…A diagram and description of the manual review process are provided in an earlier article. 8 Cross-validation was used for the initial assessment of learning algorithms and for the experiments on pruning methods. Smaller training sets are more likely to be biased by particular features of the data and therefore suffer from overfitting.…”
Section: Methodsmentioning
confidence: 99%
“…7 The overall quality of AstraZeneca's corporate compound collection is monitored by Compound Management (CM). The purity and structural identity of compounds entering the collection are established using reversed-phase high-performance chromatography coupled with MS with an additional CAD to measure concentration, 8 hereafter referred to as the LC-MS system. In addition, LC-MS activities are required to support the formation of screening collections for high-throughput screening (HTS) campaigns as well as the provision of "just in time" analysis to support later-stage screening projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published work covering chemical instability in DMSO has been limited, 48 and attempts to build a predictive model have been only partially successful. 9,10 This is not surprising, considering the range of chemistries involved.…”
Section: Introductionmentioning
confidence: 99%